2020
DOI: 10.1021/acs.chemmater.0c01199
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuric Acid Electrolyte Impacts Palladium Chemistry at Reductive Potentials

Abstract: We report herein that sulfuric acid electrolyte affects the kinetics of hydrogen sorption and desorption, the amount of absorbed hydrogen, and the electrocatalytic activity of palladium using X-ray photoelectron spectroscopy (XPS) and in situ temperature-programmed desorption (TPD). This study utilized a custom TPD instrument tailored to the in situ characterization of palladium films electrochemically saturated with absorbed hydrogen (PdH x for x > 0.6), and we present the first experimental data for the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The formate mechanism involves a proton-coupled electron transfer (PCET) process, during which the proton transfer and electron transfer occur in a same elementary step, and the M−H bond is formed on the surface 51 , 52 . Although H adsorption on the surface is thermodynamically more favorable (by 0.33 eV) compared to subsurface H absorption (which leads to hydride formation), H could diffuse into the subsurface and then bulk fcc Pd lattice at more negative potentials 18 , 53 , 54 . The overall hydrogen sorption process within Pd and Pd 4 Ag systems can be described by 55 : where the diffusion between H ads and H subsurface follows the equilibrium that is determined by the chemical potentials of H atoms in each phase ( μ Hads vs. μ Hsubsurface ).…”
Section: Resultsmentioning
confidence: 99%
“…The formate mechanism involves a proton-coupled electron transfer (PCET) process, during which the proton transfer and electron transfer occur in a same elementary step, and the M−H bond is formed on the surface 51 , 52 . Although H adsorption on the surface is thermodynamically more favorable (by 0.33 eV) compared to subsurface H absorption (which leads to hydride formation), H could diffuse into the subsurface and then bulk fcc Pd lattice at more negative potentials 18 , 53 , 54 . The overall hydrogen sorption process within Pd and Pd 4 Ag systems can be described by 55 : where the diffusion between H ads and H subsurface follows the equilibrium that is determined by the chemical potentials of H atoms in each phase ( μ Hads vs. μ Hsubsurface ).…”
Section: Resultsmentioning
confidence: 99%
“…TPD samples were prepared by electrochemically loading hydrogen into the catalyst‐coated membrane in 0.1 M HCl at a potential of −0.4 V (vs. Ag/AgCl) until a total charge of 10 C was passed. HCl was chosen over H 2 SO 4 because SO 4 2− has been demonstrated to strongly adsorb on palladium and slow H desorption kinetics [26] . This electrochemical protocol was designed to saturate the sample with absorbed hydrogen (H abs ).…”
Section: Resultsmentioning
confidence: 99%
“…HCl was chosen over H 2 SO 4 because SO 4 2À has been demonstrated to strongly adsorb on palladium and slow Hd esorption kinetics. [26] This electrochemical protocol was designed to saturate the sample with absorbed hydrogen (H abs ). Thes amples were immediately quenched in liquid nitrogen for 30 safter loading to suppress immediate desorption of H abs before transfer into the TPD chamber.Hydrogen desorption was then monitored by the atm-MS while the temperature was increased at arate of 10 Kmin À1 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that hydrogen, due to its extremely small atomic radius, can easily penetrate metal layers. , For example, Sorok et al reported that hydrogen can pass through a 7 nm Ru metal layer . On the other hand, hydrogen can also pass through metal layers or be directly stored in the Pd lattice. Utilizing these unique properties of hydrogen is a promising approach to solve scientific problems faced by the HOR. , In this paper, we used Ru monolayer grown on Au@Pd core–shell nanoparticles as a HOR catalyst under alkaline conditions, which exhibited high activity comparable to Pt as well as excellent CO tolerance. Furthermore, the activity of Ru-based catalysts with triple-layered core–shell nanostructures is negatively correlated with the thickness of the intermediate Pd layer (the catalyst is denoted as Au@Pd x @Ru, where x represents Pd layer thicknesses of 0.8, 3.5, and 6.3 nm).…”
Section: Introductionmentioning
confidence: 99%